Late Pleistocene carnivores (Carnivora: Mammalia) from a cave sedimentary deposit in northern Brazil - RODRIGUES,SHIRLLEY (2014)
The Brazilian Quaternary terrestrial Carnivora are represented by the following families: Canidae, Felidae, Ursidae, Procyonidae Mephitidae and Mustelidae. Their recent evolutionary history in South America is associated with the uplift of the Panamanian Isthmus, and which enabled the Great American Biotic Interchange (GABI). Here we present new fossil records of Carnivora found in a cave in Aurora do Tocantins, Tocantins, northern Brazil. A stratigraphical controlled collection in the sedimentary deposit of the studied cave revealed a fossiliferous level where the following Carnivora taxa were present: Panthera onca, Leopardus sp., Galictis cuja, Procyon cancrivorus, Nasua nasua and Arctotherium wingei. Dating by Electron Spinning Resonance indicates that this assemblage was deposited during the Last Glacial Maximum (LGM), at least, 22.000 YBP. The weasel, G. cuja, is currently reported much further south than the record presented here. This may suggest that the environment around the cave was relatively drier during the LGM, with more open vegetation, and more moderate temperatures than the current Brazilian Cerrado.